The challenges of sustained development : the role of socio-cultural factors in East-Central Europe - Adam, Frane (Central European University Press, 2005)
How wide is the gap between the new democracies of East-Central Europe and the most developed European nations? How can it be narrowed? The book is trying to address these issues in a comprehensive way, taking into account not only economical but socio-cultural and political aspects of development.